Tapping the Potential of Bolivia's Agriculture and Food Systems to Support Inclusive and Sustainable Growth - World Bank (World Bank, Washington, DC, 2021)
Agriculture and the rural space will continue to demand the attention of policy makers in Bolivia for several reasons, even as urbanization gains momentum. First, agriculture is a proven engine of economic growth. Aside from showing its strength in decades past, in recent years agriculture shielded the Bolivian economy from the worst effects of the decline in other primary sectors, and in the future, healthy rates of agricultural growth will make the overall economy more diversified and more resilient. Second, a robust and dynamic agricultural sector will continue to curb dependence on the mining and gas sectors, while contributing significantly to inclusive growth, value addition, the creation of more and better jobs on and off of the farm, and better nutrition for all. Third, because agricultural growth in Bolivia has proven to be pro-poor, maintaining that growth is essential for continued reductions in poverty. Fourth, because climate and other shocks affecting agriculture can significantly disrupt steady gains in economic growth, poverty reduction, and food security, building a resilient agricultural sector is critical to sustain those gains. Finally, although policy makers will want to support agricultural growth, they will not want that growth to compromise the future for generations of Bolivians by squandering and degrading irreplaceable natural resources.